Positioning Based on Factor Graphs. (26th June 2007) - Mensing Mensing, Christian Christian; Plass Plass, Simon Simon
Abstract : This paper covers location determination in wireless cellular networks based on time difference of arrival (TDoA) measurements in a factor graphs framework. The resulting nonlinear estimation problem of the localization process for the mobile station cannot be solved analytically. The well-known iterative Gauss-Newton method as standard solution fails to converge for certain geometric constellations and bad initial values, and thus, it is not suitable for a general solution in cellular networks. Therefore, we propose a TDoA positioning algorithm based on factor graphs. Simulation results in terms of root-mean-square errors and cumulative density functions show that this approach achieves very accurate positioning estimates by moderate computational complexity.